Pengaruh Integritas Dan Profesionalisme Terhadap Kinerja Pegawai Badan Pendapatan Daerah Kota Tasikmalaya - Irma Andini; Barin Barlian; Gian Riksa Wibawa (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research was conducted to determine the Influence of Integrity and Professionalism on the Performance of Employees of the Local Revenue Agency of Tasikmalaya City. This study used a quantitative approach with Associative (Causal) research methods using data obtained directly through questionnaires distributed to 47 repondents. The technique used in this research is multiple linear regression. The results of the study indicate that: (1) Integrity and Professionalism simultaneously have a significant effect on Employee Performance: (2) Integrity partially has a significant effect on Employee Performance: (3) Professionalism partially has a significant effect on Employee Performance